Sex differences in predictors and outcomes of camouflaging: comparing diagnosed autistic, high autistic trait and low autistic trait young adults - Milner, V; Mandy, W; Happé, F; Colvert, E (SAGE Publications, 2022)
Many autistic individuals camouflage socially atypical behaviours. Evidence suggests autistic females camouflage more than autistic males. Although camouflaging may confer some benefits, it is also associated with negative outcomes including poorer mental health and well-being. Those with high autistic traits but no clinical diagnosis are not seldom included in camouflaging research, therefore we cannot ascertain whether camouflaging plays a role in the underdiagnosis of autistic females. Data from young adults with a diagnosis of autism (n = 78), high autistic traits but no diagnosis (n = 177) or low autistic traits (n = 180) revealed autistic females reported camouflaging significantly more than other groups. Males and females with low autistic traits reported significantly lower camouflaging than high trait and diagnosed groups. Loneliness was a key predictor of camouflaging for the diagnosed group only. Camouflaging was found to predict lower psychological quality of life for the diagnosed group, and lower social quality of life for the high trait and low trait groups. Overall, findings indicated that, although all groups reported camouflaging, the motivations for doing so may be different for diagnosed autistic individuals. It is important for stakeholders and society to improve understanding of autism and acceptance of atypical behaviour to alleviate possible negative outcomes associated with camouflaging.